Investigation on flow characteristics of the multi-channel confluent water supply in firefighting - Ge Zhao; Xing Zhang; Kang Liang; Yutan Li; Depeng Sun (Advances in Mechanical Engineering)
The multi-channel concentrated water supply system represents a pivotal link in the firefighting water supply chain, and ensuring the efficiency of its water supply is of paramount importance for the smooth progress of firefighting. A mathematical model is established for the steady state and transient conditions of the multi-channel water supply system. The model solution indicates that the number of parallel channels, centrifugal pump operating frequency, valve execution time, and system resistance can affect the output pressure and flow rate of the confluent water supply system. A detailed investigation was performed into the influence laws of different operating parameters on the output characteristics of the multi-channel confluent water supply system, based on the experimental and simulation research platform. Especially under transient conditions, the increase in the operating frequency and valve switching interval will result in a greater value for the main pipe pressure drop/pressure rise. When the load valve opening is below 50%, the influence of the valve switching interval time and channel transported distance on the pressure drop value is reduced. The research results provide a foundation for the smooth switching of multi-channel confluent water supply systems.